Effectiveness, safety and efficacy of INTELLiVENT–adaptive support ventilation, a closed–loop ventilation mode for use in ICU patients – a systematic review - Botta, M; Wenstedt, EFE; Tsonas, AM; Buiteman-Kruizinga, LA; van Meenen, DMP; Korsten, HHM; Horn, J; Paulus, F; Bindels, AGJH; Schultz, MJ; De Bie, AJR (Taylor and Francis, 2021)
Introduction: INTELLiVENT–Adaptive Support Ventilation (INTELLiVENT–ASV), an advanced closed–loop ventilation mode for use in intensive care unit (ICU) patients, is equipped with algorithms that automatically adjust settings on the basis of physiologic signals and patient’s activity. Here we describe its effectiveness, safety, and efficacy in various types of ICU patients.